Dynamics of Dairy Cow Milk Production in Semarang Regency during the New Order Era - Chabibul Wahab; Shokheh, Mukhamad (Program Studi Pendidikan Sejarah - Universitas Samudra, 2026)
During the New Order era, the Indonesian government introduced the Green Revolution concept as an effort to increase agribusiness sector yields with the goal of food self-sufficiency. In the livestock sector, the Green Revolution was adopted into a program called Panca Usaha Ternak (PUT). This study seeks to expose the dynamics of government program realization during the New Order period. The method in this study involves an analysis of literature sources relevant to the theme of milk production in Indonesia, specifically during the New Order period. This study uses primary and secondary sources. The primary sources of this study use data from the BPS (Central Bureau of Statistics) and the Livestock Service of Central Java Province, while the secondary sources consist of books and articles in several journals. In determining relevant sources, verification steps were carried out by comparing various types of data obtained. This study found the fact that in Semarang Regency, there was a significant surge in milk production and an increase in the dairy cow population, especially after the issuance of the Joint Decree (SKB) of three ministers in 1983. Nevertheless, in 1998, IMF intervention caused the absorption ratio regulation to be forcibly abolished by the government